Bystander interventions against gender-based violence and harassment in the workplace: a scoping review - Nielsen, Kristan Stampe; Hansen, Maj; Mikkelsen, Eva Gemzøe (Frontiers in Psychology, 2025)
Gender-based violence and harassment (GBVH) has detrimental effects on organisational performance and employee well-being. Primary-level bystander intervention programmes that enable employees to act when witnessing GBVH offer a promising prevention strategy. Despite the increased focus on the importance of primary-level bystander interventions, limited efforts have been made to systematically synthesise research in this area. The present scoping review therefore sought to consolidate research on primary-level bystander interventions implemented in organisations by exploring the theoretical frameworks used to develop these interventions, determining outcomes, and examining facilitators and obstacles for their implementation. Five databases [Embase (Ovid), MEDLINE (Ovid), Scopus, Web of Science, and PsycINFO (Ovid)], and grey literature were systematically searched. Out of 11.302 references screened, 14 studies were included in the present scoping review. Findings suggest that primary-level bystander interventions, particularly bystander training workshops incorporating practice exercises, can increase prosocial bystander behaviour. However, the paucity of follow-up measurements makes it challenging to evaluate their long-term efficacy. The included studies underscore the importance of tailoring interventions to specific workplace contexts. While comprehensive program theories underpin most studies, organisational change theories were typically absent, even when interventions aimed to achieve cultural change. In conclusion, this review emphasises the significance of bystander interventions for primary GBVH prevention and underscores the need for further research to identify optimal practices and ensure enduring effectiveness.Systematic review registrationThe protocol is registered on the Open Science Framework website at https://osf.io/3pt5k/.